Database encryption for a web-based claims system - Syed Zulkarnain bin Syed Idrus (Universiti Malaysia Perlis (UniMAP), 2008)
This thesis is about the development of a computer system for institutions of higher learning particularly Public Institutions of Higher Learning (PIHL) so that staff can make online claims for official outstation duties. In fact, this system will be able to take over the whole administration of staff's travel claims within Malaysia, including Sabah and Sarawak. The development of this system is based on the Treasury Circulars issued by the Ministry of Finance, Malaysia or other circulars related to it. The system must be promptly updated once there are amendments with regards to the Treasury Circulars. This system can also be applied to other government's departments. Apart from that, a security aspect of the system will be analysed for its effectiveness and performance, thus provide the necessary prevention from intruders that might want to steal data within the system.